2008
DOI: 10.1103/physreva.78.032515
|View full text |Cite
|
Sign up to set email alerts
|

Hartree-Fock-Roothaan calculations for many-electron atoms and ions in neutron-star magnetic fields

Abstract: The quantitative analysis of the electromagnetic spectra of isolated neutron stars by means of model atmosphere calculations requires extensive data sets of atomic energy values and transition probabilities in intense magnetic fields. We present a new method for the fast computation of wave functions, energies, and oscillator strengths of medium-Z atoms and ions at neutron star magnetic field strengths B 10 7 T which strikes a balance between numerical accuracy and computing times. We use a Hartree-Fock ansatz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…These orbitals are products of a spatial wave function ψ i (r) and a spin function χ i (s). In a previous version of the Hartree-Fock-Roothaan method [29,30], the single-electron wave functions were taken in the form of a product,…”
Section: A Two-dimensional-hartree-fock-roothaan Equationsmentioning
confidence: 99%
“…These orbitals are products of a spatial wave function ψ i (r) and a spin function χ i (s). In a previous version of the Hartree-Fock-Roothaan method [29,30], the single-electron wave functions were taken in the form of a product,…”
Section: A Two-dimensional-hartree-fock-roothaan Equationsmentioning
confidence: 99%
“…The comparison of oscillator strengths of transitions to the carbon ground state in Table V of Ref. [49] and of transitions to the ground states of iron ions in Table VI shows that the improvements are large only for transitions with very small oscillator strengths, while for large oscillator strengths taking into account more Landau levels does not significantly change the values calculated in adiabatic approximation. Thus it may be concluded that the energies and oscillator strengths calculated using the HFFEM code already well reproduce the general features of the exact level scheme.…”
Section: Results and Accuraciesmentioning
confidence: 93%
“…[49,50] where they are compared with the results of more advanced (but slower) methods as a function of magnetic field strength and nuclear charge.…”
Section: Results and Accuraciesmentioning
confidence: 99%
See 2 more Smart Citations